The role of culture in enhancing well-being and soft skills: from passive to active participation - Alessandra Passaretti; Luigi Aruta; Chiara Scuotto; Ferdinando Ivano Ambra (Firenze University Press, 2023)
The 2030 Agenda has among its sustainability goals the promotion of health and well-being. These goals seem to depend on disparate interdependent factors, including psychological well-being, the ability to self-determine, and the social cohesion of the context in which an individual grows and develops. Cultural participation seems to be an effective response to this challenge, as it can promote the development of personal and social skills. In the present article it is, therefore, analyzed how active and/or passive participation in cultural activities can represent an interesting educational ground for promoting well-being through the development of soft skills. At the same time, the neurobiological effects of such enjoyment and an examination of the most effective pedagogical interventions are reported.   Il ruolo della cultura nel potenziare il benessere e le soft skills: da partecipazione passiva ad attiva. L'agenda 2030 ha tra i suoi obiettivi di sostenibilità la promozione della salute e del benessere. Questi obiettivi sembrano dipendere da disparati fattori interdipendenti tra loro, tra cui il benessere psicologico, la capacità di autodeterminarsi, nonché la coesione sociale del contesto all'interno del quale un individuo cresce e si sviluppa. La partecipazione culturale sembra rappresentare una risposta efficace a questa sfida, in quanto in grado di promuovere lo sviluppo di competenze personali e sociali. Nel presente articolo è, quindi, analizzato come la partecipazione attiva e/o passiva alle attività culturali possa rappresentare un interessante terreno educativo per promuovere il benessere attraverso lo sviluppo di soft-skills. Allo stesso tempo sono riportati gli effetti neurobiologici di tale fruizione ed una disamina sugli interventi pedagogici più efficaci.